Understanding of Physical Activity in Social Ecological Perspective: Application of Multilevel Model - Lee, Yoongu; Park, Sanghyun (Frontiers in Psychology, 2021)
In the social ecological model, personal characteristics are important determinants of health behaviors, however, multi-dimensional approaches that consider social and physical environments must be utilized to gain a broader picture. Accordingly, this study examines the effects of personal, social, and physical environment variables as factors affecting levels of physical activity (METs). Our findings are based on 72,916 responses from the 2015 Community Health Survey in South Korea. Individual characteristics considered included sex, education level, marital status, age, and income. The social environment variables considered were trust between neighbors and the social network with neighbors. The physical environment variables were satisfaction with living environment and satisfaction with public transportation. The analysis was conducted using a multilevel model in order to accurately consider the characteristic differences of the variables. Regarding personal characteristics, sex, education level, and age have a significant effect on physical activity. Of the social and physical environment variables, social network with neighbors and satisfaction with public transportation have a significant effect on physical activity. This study confirms that a macroscopic understanding is needed to explain individual levels of physical activity; the results of this study will be helpful for public health interventions concerning physical activity.